New Technologies Provide Quantum Changes in the Scale, Speed, and Success of SELEX Methods and Aptamer Characterization - Abdullah Ozer; John M Pagano; John T Lis (Elsevier, 2014)
Single-stranded oligonucleotide aptamers have attracted great attention in the past decade because of their diagnostic and therapeutic potential. These versatile, high affinity and specificity reagents are selected by an iterative in vitro process called SELEX, Systematic Evolution of Ligands by Exponential Enrichment. Numerous SELEX methods have been developed for aptamer selections; some that are simple and straightforward, and some that are specialized and complicated. The method of SELEX is crucial for selection of an aptamer with desired properties; however, success also depends on the starting aptamer library, the target molecule, aptamer enrichment monitoring assays, and finally, the analysis and characterization of selected aptamers. Here, we summarize key recent developments in aptamer selection methods, as well as other aspects of aptamer selection that have significant impact on the outcome. We discuss potential pitfalls and limitations in the selection process with an eye to aid researchers in the choice of a proper SELEX strategy, and we highlight areas where further developments and improvements are desired. We believe carefully designed multiplexed selection methods, when complemented with high-throughput downstream analysis and characterization assays, will yield numerous high-affinity aptamers to protein and small molecule targets, and thereby generate a vast array of reagents for probing basic biological mechanisms and implementing new diagnostic and therapeutic applications in the near future.